Kolaborasi Tri Pusat Pendidikan (Keluarga, Sekolah, Dan Masyarakat) Dalam Pengembangan Potensi Anak - Ghozali, Muhammad; Hasta Ayu Pribawanti; Agus Tinus (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2026)
This study analyzes the collaborative role of the three educational centers, namely family, school, and community, in developing children’s potential. The study used an integrative literature review by synthesizing 22 recent articles published between 2023 and 2025 in Indonesian education journals indexed in Sinta 2. The analysis focused on four domains: family learning support, school partnership mechanisms, community and local-wisdom-based learning, and the development of children’s literacy, character, creativity, social maturity, and inclusive learning participation. The findings show that family involvement strengthens children’s literacy habits, learning routines, emotional support, and continuity between school and home. Schools play a central role in organizing communication, learning design, character programs, and inclusive support systems. Communities enrich learning through local culture, service learning, social values, and contextual resources. The study concludes that children’s potential develops optimally when the three centers work reciprocally through shared goals, respectful communication, culturally responsive pedagogy, and continuous monitoring of children’s academic and socio-emotional growth.